(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to evaluate the effect of bioenzymatic treatment of low-quality feeds on the production performance of Barqawi sheep in the eastern region of Libya, with a focus on the cities of: Al-Bayda, Al-Qubba, and Derna. The experiment included 100 Barqawi sheep, distributed into five equal groups according to a completely randomized design (CRD). It included a control group whose feed was not treated, and a treatment group with Fibrolytic enzymes or a Fibrolytic+proteolytic mixture, with different methods of addition between spraying and direct mixing. Daily weight gain (ADG), feed intake (DMI), digestibility of dry matter and fiber (ADF digestibility, DM, NDF), and feed conversion efficiency (FCR) were evaluated during an experimental period that lasted three months following an adaptation period of 10-14 days. The results showed that enzyme treatment led to a significant increase in (ADG) by (25-40%) compared to the control group, with a clear improvement in the digestibility of dry matter and fiber by (10-15%), and an improvement in feed conversion results by 1.5-2 kg of feed/kg of weight gained. No negative effects on animal health were observed, and the health of all sheep remained good throughout the experiment. These results indicate that enzymatic treatment of low-quality feed is an effective means of improving the productive and economic performance of Barqawi sheep in the Libyan environment.